Sistem Informasi Penjualan Mebel Pada Toko Jepara Kotapinang Berbasis Web - Ningsih, Ayu (Universitas Labuhanbatu, 2021)
Jepara shop is a company engaged in the field of furniture production, especially in teak wood. The problem in this study is that consumers are still difficult to get information on products offered by Jepara Stores, so consumers must come directly to Jepara Stores. To get information about the products being marketed, therefore the author makes a web-based marketing system that can help to obtain information, so that it can easily access the website whenever you want, besides that with online sales are expected to improve service to consumers.